THE PROHIBITION OF WOMEN TO WORK IN MICHAEL PETRONI’S MOVIE THE BOOK THIEF - Ayu Wandari Sabahtini; Agnes Widyaningrum (Dinamika Bahasa dan Budaya, 2020)
The study focuses on the prohibition of women to work that are experienced by the female characters depicted in The Book Thief movie. The prohibition of women to work has many reasons. One of the reasons is that they cannot have the same opportunity to determine their wish, not just in work but also in education. The limitation in having jobs for women is because of the limited education that they have. Which is the education for women is usually categorized as women’s education that is related to the housework considered as appropriate education for women. The method in this study is essentially qualitative research with content analysis technique in The Book Thief movie script by collecting certain information that relates to the research questions on the prohibition of women to work, based on feminism theory by Mary Wollstonecraf “A Vindication of the Right Of Women”. Finding of the study shows that education for women has an important role, such as economic growth and also for the welfare of their own family. If women do not have enough education it will hamper them from the opportunity of employment, with those opportunities they can help their family's economic condition. Key words: Women’s work, Education, Gender equality, Women’s Rights